2017
DOI: 10.1037/lhb0000242
|View full text |Cite
|
Sign up to set email alerts
|

Crime seriousness and participation in restorative justice: The role of time elapsed since the offense.

Abstract: Acknowledgments:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
(126 reference statements)
1
13
1
1
Order By: Relevance
“…Research has shown that different crimes can activate different values, and values only influence behaviour when they are relevant in that context, therefore the expression of values during the restorative justice process may be dependent on the circumstances of the crime (Feather, 1998;Schwartz, 2012). Specifically, the type of offence that occurred, perceived severity of the offence, relationship history, and the time that has elapsed have all been shown to influence the likelihood of a victim taking part in restorative justice (Batchelor, 2017;Feather, 1998;Paul, 2015;Zebel et al, 2017). Facilitators in this study often stated that the presence of characteristics reflective of values were dependent upon the type of case and found it much easier to discuss the importance of things in the lives of specific individuals, which suggests that these factors may be moderating any relationship between values and restorative justice participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that different crimes can activate different values, and values only influence behaviour when they are relevant in that context, therefore the expression of values during the restorative justice process may be dependent on the circumstances of the crime (Feather, 1998;Schwartz, 2012). Specifically, the type of offence that occurred, perceived severity of the offence, relationship history, and the time that has elapsed have all been shown to influence the likelihood of a victim taking part in restorative justice (Batchelor, 2017;Feather, 1998;Paul, 2015;Zebel et al, 2017). Facilitators in this study often stated that the presence of characteristics reflective of values were dependent upon the type of case and found it much easier to discuss the importance of things in the lives of specific individuals, which suggests that these factors may be moderating any relationship between values and restorative justice participation.…”
Section: Discussionmentioning
confidence: 99%
“…Paul (2015) suggests that the decision by victims and offenders to participate is determined by a variety of situational, personal, and relational factors. Some situational factors which have received attention to date are that of offence seriousness and time since the offence (Batchelor, 2017;Zebel, Schreurs, & Ufkes, 2017).…”
Section: Role Of Personal Values In the Restorative Justice Processmentioning
confidence: 99%
“…19 De gedachte dat het welzijn van het slachtoffer recht evenredig samenhangt met het lijden van de dader, hetgeen als vertrekpunt geldt binnen het opgeld doende punitief-populistische slachtofferbeleid, is een doodlopende straat. 20 Het zou goed zijn op een volgend congres ook het herstelrecht nadrukkelijk te agenderen als zijnde een voor het slachtoffer belangrijke aanspraak. Bijkomend voordeel is dat daarmee uitvoering zou worden gegeven aan Aanbeveling 2018/8 inzake de toepassing van herstelrecht in strafzaken.…”
Section: Hoe Nu Verder?unclassified
“…While RJ appears to be a promising alternative or complementary form of justice, including during incarceration, scholars are concerned that without support by the public, victims, and perpetrators, it may decline (Gavrielides, 2016; Moss et al, 2019), or be limited to minor offenses (Hoyle & Rosenblatt, 2016). For example, if victims and perpetrators do not adopt favorable attitudes toward RJ, they might be unwilling to meet (Peleg-Koriat & Weimann-Saks, 2019; Zebel et al, 2017). Likewise, negative attitudes might preclude community participation, which is key to the process, as aforementioned (Hoyle & Rosenblatt, 2016; Rossner & Bruce, 2016).…”
Section: Introductionmentioning
confidence: 99%